Adapting to climate change: Increasing the flow of data - Tarhule, Aondover; Saley-Bana, Zakari; Lamb, Peter J. (Technical Centre for Agricultural and Rural Cooperation, 2011)
Climate researchers have developed a system that uses GIS, computers, and the internet to improve rainfall data management and information delivery to farmers in West Africa.